Switching to Progressively Reduced Nicotine Content Cigarettes in Smokers With Low Socioeconomic Status: A Double-Blind Randomized Clinical Trial. Issue 6 (29th November 2020) - Krebs, Nicolle M; Zhu, Junjia; Wasserman, Emily; Kuprewicz, Robin; Martinez, Diane J; Veldheer, Susan; Livelsberger, Craig; Modesto, Jennifer; Reinhart, Lisa; Trushin, Neil; Reilly, Samantha M; Liao, Jason; et al.
Abstract: Introduction: The Food and Drug Administration issued an advanced notice of proposed rulemaking for setting a product standard for nicotine levels in cigarettes, with an emphasis on minimally or non-addicting very low nicotine content (VLNC). Methods: A 33 week, two-arm, double-blind randomized trial conducted in Hershey, Pennsylvania, USA and Washington, DC, USA included adult daily cigarette smokers (≥5 cigarettes per day) with less than a college degree, and who had no plans to quit within the next six months. Participants were randomized to either reduced nicotine content (RNC) study cigarettes tapered every three weeks to a final VLNC (0.2 mg/cigarette) for six weeks or to usual nicotine content (UNC) study cigarettes (11.6 mg/cigarette). Outcomes included acceptability of study cigarettes measured by attrition (primary outcome), compliance, reduction in cigarette dependence and tobacco biomarkers, and post-intervention cessation. Results: The RNC ( n = 122) versus UNC ( n = 123) group had higher attrition (adjusted Hazard Ratio 3.4; 95% confidence interval [CI] 1.99 to 5.81). At the end of the intervention, cotinine levels were 50% lower in the RNC group (mean group difference −137 ng/mL; 95% CI −172, −102). The RNC group smoked fewer CPD (−4.1; 95% CI −6.44, −1.75) and had lower carbon monoxide levels (−4.0 ppm; 95% CI −7.7, −0.4). Forty seven percent (29/62) of the RNC group were biochemically-confirmed compliant with smoking VLNC cigarettes (mean cotinine = 8.9 ng/ml). At three month follow-up, only compliant VLNC smokers quit with an assisted quit attempt ( N = 6/22, 27%). Conclusions: This study supports a VLNC standard in cigarettes. Implications: Differential dropout and noncompliance indicate some smokers had difficulty transitioning to cigarettes with reduced nicotine. These smokers will benefit from supplemental nicotine in medicinal or noncombustible tobacco products if a nicotine reduction standard is established. Other smokers successfully transitioned to very low nicotine content cigarettes exclusively and substantially reduced their exposure to nicotine.